2019
DOI: 10.1161/jaha.119.012594
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker Implantation and Dependency After Transcatheter Aortic Valve Replacement in the REPRISE III Trial

Abstract: BackgroundAs transcatheter aortic valve replacement expands to younger and/or lower risk patients, the long‐term consequences of permanent pacemaker implantation are a concern. Pacemaker dependency and impact have not been methodically assessed in transcatheter aortic valve replacement trials. We report the incidence and predictors of pacemaker implantation and pacemaker dependency after transcatheter aortic valve replacement with the Lotus valve.Methods and ResultsA total of 912 patients with high/extreme sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 27 publications
9
44
1
5
Order By: Relevance
“…The nine remaining studies identified risk factors for 30-day PPI as summarized in Table 2 [ 12 20 ]. Meduri et al identified preexisting RBBB, female sex, and depth of implantation to be a risk factors for 30-day PPI in their retrospective review of the REPRISE III (The Repositionable Percutaneous Replacement of Stenotic Aortic Valve through Implantation of Lotus Valve System-Randomized Clinical Evaluation) trial [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nine remaining studies identified risk factors for 30-day PPI as summarized in Table 2 [ 12 20 ]. Meduri et al identified preexisting RBBB, female sex, and depth of implantation to be a risk factors for 30-day PPI in their retrospective review of the REPRISE III (The Repositionable Percutaneous Replacement of Stenotic Aortic Valve through Implantation of Lotus Valve System-Randomized Clinical Evaluation) trial [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nine remaining studies identified risk factors for 30-day PPI as summarized in Table 2 [ 12 20 ]. Meduri et al identified preexisting RBBB, female sex, and depth of implantation to be a risk factors for 30-day PPI in their retrospective review of the REPRISE III (The Repositionable Percutaneous Replacement of Stenotic Aortic Valve through Implantation of Lotus Valve System-Randomized Clinical Evaluation) trial [ 12 ]. Nazif et al identified preexisting RBBB, prosthesis to left ventricular outflow tract diameter ratio, and left ventricular end-diastolic diameter as risk factors for 30-day PPI in their retrospective review of the PARTNER (Placement of AoRtic TraNscathetER Valves) trial [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that periodic examination and adjustment of pacemaker settings minimised the risk of long-term pacing in patients requiring PMI after TAVI. 75 Prior studies also showed pacemaker dependency after TAVI was not so high. 28,59 Thus, leadless pacemakers may contribute to less morbidity in these patients.…”
Section: Choice Of Pacemakermentioning
confidence: 99%
“…Permanent pacemaker rates have also been higher in TAVI patients, particularly with the self-expanding valves. 38 While pacing rates seem to be lower in younger patients (with healthier cardiac conducting systems) as demonstrated in the PARTNER 3 study, there is concern that pacing will have a greater impact in the treatment of younger patients who may need multiple generator changes throughout their lifetimes and be subject to longer term right ventricular pacing.…”
Section: Introductionmentioning
confidence: 99%